Active fault tolerant tracking control of turbofan engine based on virtual actuator. (March 2022) - Ma, Yan-Hua; Du, Xian; Sun, Xi-Ming; Zhao, Fang-Jiao
Abstract: In this paper, an active fault-tolerant tracking control scheme for the turbofan engine under dynamic and simultaneous actuator faults and sensor faults under disturbances is proposed. First, based on the linear parameter-varying model of the turbofan engine, an H ∞ state feedback nominal controller is designed so as to achieve rotor speed tracking control with adaptive gain scheduling characteristics at different working conditions for the turbofan engine. Next, for the control system with simultaneous multiplicative actuator faults and additive sensor faults, a virtual actuator based active fault-tolerant tracking control strategy is developed to reconfigure the system such that it can obtain the similar behavior to the fault-free system without modifying the nominal controller. Specifically, in addition to handle the actuator fault by the virtual actuator, the reconfigured controller adopts a feedforward control signal to compensate for the sensor fault. Besides, in order to guarantee the reconfigured system, a sufficiency criterion is proposed. Finally, simulations have been conducted on a twin-spool turbofan engine to verify the effectiveness of the strategy. Highlights: An active fault tolerant tracking control strategy is proposed for turbofan engine. The strategy is based on virtual actuator to deal with sensor and actuator faults. The virtual actuator is extended to the proposed H ∞ state feedback controller. Sufficient conditions are given to ensure the stability of the reconfigured system. The proposed control strategy is verified on a military turbofan engine.